The Business of iPhone App Development Making and Marketing Apps that Succeed - Wooldridge, Dave (Apress, 2013)
The mobile landscape is very different than it was just a few years ago. The iPhone’s powerful software, revolutionary user interface, and powerful developer platform has driven an almost overnight explosion of apps. Consumers have shown through their actions that apps are how they want to consume content on mobile devices. The rapid change in the mobile landscape provides an excellent opportunity for entrepreneurship. In June 2008, I left a nearly four-year tenure at Apple because on the eve of the App Store launch, I felt the old guard of the mobile industry, who had been the gatekeepers, were about to lose their stranglehold, giving way to a new generation of entrepreneurs. My adventure in the iPhone space has been highly rewarding emotionally, intellectually, and, yes, financially. I have also never worked harder in my life. My firm, Double Encore, has been offering iPhone consulting and development services since July 2008. Since that time, I have met with a countless number of perspective clients from individuals to large brands. There is no shortage of enthusiasm and optimism. Yet the App Store is not the fountain of youth. Nor can it turn coal into gold. There are many more failures than successes in this young market. To be successful in the new mobile industry, you must not merely develop an app. You need to own the enter life cycle of your app from conception, design, development, and ultimately distribution. The journey doesn’t end when your app appears on the App Store. Your job is to figure out where the rubber meets the road, to paraphrase an entrepreneurial expression. Have you done market research to determine whether you’re addressing a need in the market place? How big is the addressable market? How are you going to generate revenue? How are you going to market the app? Why is your app better? These are some of the key questions you should be asking while you are considering building an iPhone application business. I have seen too many people, some of whom were my own clients, who put too much faith in the App Store to sell their product for them. There is good news! The Business of iPhone App Development is the most comprehensive, easy-to-use resource for planning a sustainable iPhone application business. The book is extremely thorough and will guide you through the critical onsiderations you will face. From generating buzz to defining your business model, The Business of iPhone App Development offers a depth and breadth of knowledge that I believe will equip you with the tools necessary to achieve success. Are you ready?